PENGGUNAAN LAGU BAHASA INGGRIS DALAM MEMBINA KETERAMPILAN PENGUCAPAN DI PUSAT BIMBINGAN BELAJAR BAHASA INGGRIS UNTUK SISWA KAPAL PESIAR - Faradilla Arisya Azwa; Salsabila Rayhananda Bachty; Wahyu Indah Mala Rohmana (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2025)
This study explores the effectiveness of using music to improve the development of pronunciation skills in English language learning. Using qualitative descriptive methods, this study involved interviews with English teachers at the English Tutoring Centers for Cruise Students in Bangkalan to investigate the integration of music in the development of pronunciation skills in English language learning. The main goal is to identify the experiences, benefits, and obstacles faced by educators and students when using music as a tool to develop pronunciation skills in English language learning. Researchers show that music integration is an innovative and effective approach that presents a fun learning atmosphere, correct English pronunciation, and increased motivation in English learning. Despite facing challenges such as accent differences and intonation speed in the pronunciation of words in music, this study confirms the great potential of music in improving pronunciation skills in English language learning. Continuous efforts in adapting learning strategies and providing support and advice are essential to maximize the benefits of using music in the development of pronunciation skills and pave the way for improved English language learning.